A theoretical study of wrinkle propagation in graphene with flower-like grain boundaries. Issue 20 (17th May 2021) - Zhao, Zihui; Wang, Yafei; Wang, Changguo
Abstract : Dynamic behaviors regarding wrinkle propagation for graphene with rotational flower-like grain boundaries are investigated for the first time. Abstract : This study investigated dynamic surface wrinkle propagation across a series of flower-like rotational grain boundaries (GBs) in graphene using theoretical solutions and atomistic simulations. It was found that there was significantly less out-of-plane displacement of dynamic wrinkles when curvature of rotational GBs was reduced, which can be explained by a defect shielding effect of flower-like GBs. Potential energy evolved via different modes for pristine graphene and graphene with various GBs. With external excitation, the distinctly different patterns of wrinkle propagation in graphene with various GBs demonstrated how dynamic wrinkling can reveal defects. These results can provide a theoretical basis for guiding the design and implementation of graphene-based nano-mechanical devices such as protectors and detectors.